Affirming logistics activities toward minimizing waste in marine products based on women role in Tegal, Indonesia - Muhammad Reza; Fauzan Romadlon; Aiza Yudha Pratama; Ayu Sabrina (Institute of Computer Science (IOCS), 2022)
Women have an important role in economic development in coastal areas. One of the roles is to process the remaining marine products which are used as side activities to increase the family’ incomes. The processing activities is realized to produce added value products by minimizing marine products waste. this research aims to observe the women role in minimizing of marine products waste based on logistics activities. It is due to limited study mentioned about marine products waste assessment. The used method is quantitative with statistical test is ANOVA. The results show there is significant factor that has correlation with logistics activities. The factors are estimated amount of processed marine products and the daily income. The estimated amount of processed marine products has significant with unsold product that is given to nearest neighbor. Daily income has significant with storage, decrease the products quality, and bad weather. Moreover, by gaining appropriate storage, women have role to add their knowledge about inventory. They can collaborate with interested party to provide sufficient storage. In addition, the good storage can keep the processed marine product quality. The appropriate storage especially cold storage can keep the raw material inventory during bad weather.